The Impact of Scenario-based Settings on Cognitive Reading-to-write Processes - Yumei Zhang; Shaoqian Luo (Cranmore Publishing, 2021)
In Scenario-based assessment (SBA), a real-life scenario is created for students to do reading and writing tasks in a computer-mediated environment. It has been recognized that task authenticity will help strengthen assessment validity and task settings and characteristics will influence cognitive efforts. This study attempts to explore the underlying reading-to-write processes in an SBA setting by contrast with those in a non-SBA setting, and thereby investigate the impact of task settings on cognitive processes. Four participants were invited to complete three forms of integrated reading-writing tasks in different settings and then recall their thinking processes stimulated by screen capture recordings and their writing outcomes. The data were analyzed through parsing, encoding, and classifying. The results showed that there were differences between the processes elicited from the SBA setting and the non-SBA setting in the saliency and frequencies of some process categories, and in the ways the source texts were used. Comparatively, the processes summarized in the SBA setting were more congruent with those summarized in theoretical frameworks of integrated reading-writing processes and findings from previous studies in other contexts. The SBA setting not only encouraged a more comprehensive understanding of the multiple texts provided but also found the participants more active in making connections between new and prior ideas rather than scanning for supporting piecemeal information and patch-making. The findings affirmed the effectiveness of the authentic scenario created by computer technology, which provides insights into the constructs and validity of the assessment.